Diabetes mellitus e doença periodontal: revisão de literatura - Szendler, Cristina Baladore [UNESP] (2009)
Diabetes mellitus is an important chronic disease globally as reflected in the World Health Organization (WHO) declaring that the rate of increase in diabetes prevalence is an epidemic. In 2005, it was estimated that 217 million people were diabetic worldwide. By 2030 WHO predicts this number to increase to at least 366 million (Smyth and Heron, 2006). Current evidence regarding the biologic link between diabetes and periodontal disease supports diabetes and persisting hyperglycemia leading to an exaggerated immuno-inflammatory response to the periodontal pathogenic bacterial challenge resulting in more rapid and severe periodontal tissue destruction. Periodontitis may also be related to the glycemic control in diabetes because inflammation can increase insulin resistance. The purpose of this study is to address the relationship between diabetes mellitus and periodontal disease, as well as the plausible biologic mechanisms that support this link